2002
DOI: 10.1002/sim.1039
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approaches to establishing vaccine safety

Abstract: In a vaccine safety trial, the primary interest is to demonstrate that the vaccine is sufficiently safe, rejecting the null hypothesis that the relative risk of an adverse event attributable to the new vaccine is above a prespecified value, greater than one. We evaluate the exact probability of type I error of the likelihood score test, with sample size determined by normal approximation, by enumeration of the binomial outcomes in the rejection region and show that it exceeds the nominal level. In the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…For example, using the arcsine transformation, a similar result to (6) now gives k = 1=(1 + √ q) person years to treatment minimizes T (E) for adverse event studies, which places a smaller portion in treatment. Others have also observed that T (E) and E[N u+t ] for comparative Poisson studies of adverse events tend to be minimized with more subjects in the untreated group [7].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, using the arcsine transformation, a similar result to (6) now gives k = 1=(1 + √ q) person years to treatment minimizes T (E) for adverse event studies, which places a smaller portion in treatment. Others have also observed that T (E) and E[N u+t ] for comparative Poisson studies of adverse events tend to be minimized with more subjects in the untreated group [7].…”
Section: Discussionmentioning
confidence: 96%
“…The author thanks Bill Blackwelder for helpful discussion on this paper and two anonymous referees for very thorough review and insightful comments, including derivation of formula (7).…”
Section: Acknowledgementsmentioning
confidence: 98%
See 3 more Smart Citations